2014
DOI: 10.5688/ajpe787132
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Study of the Impact of Instructor Attitude, Enthusiasm, and Teaching Style on Student Learning in a Medicinal Chemistry Course

Abstract: Objective. To determine the effect of instructor attitude, enthusiasm, and teaching style on learning for distance and campus pharmacy students. Methods. Over a 3-year period, distance and campus students enrolled in the spring semester of a medicinal chemistry course were asked to complete a survey instrument with questions related to instructor attitude, enthusiasm, and teaching style, as well as items to measure student intrinsic motivation and vitality. Results. More positive responses were observed among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…On the one hand, experimental research has severely disrupted this consistency—null effects of enthusiastic instructions on test performance, such as those reported in the current study, have steadily mounted [2024, 27–29, 74]. On the other hand, students and educators have both become more steadfast in their endorsement of enthusiasm as a crucial aspect of effective teaching [12].…”
Section: Discussionmentioning
confidence: 91%
“…On the one hand, experimental research has severely disrupted this consistency—null effects of enthusiastic instructions on test performance, such as those reported in the current study, have steadily mounted [2024, 27–29, 74]. On the other hand, students and educators have both become more steadfast in their endorsement of enthusiasm as a crucial aspect of effective teaching [12].…”
Section: Discussionmentioning
confidence: 91%
“…39 One study found that students' intrinsic motivation and vitality-or energy with which students pursue learning-is correlated with instructor enthusiasm. 40 This intrinsic motivation has been linked to academic achievement. 41,42 Another study of online nursing courses found that student engagement was correlated with the amount of interaction and communication students had with other students and with the instructor.…”
Section: Limitations Of the Traditional Lecture Format In Neurology Ementioning
confidence: 99%
“…This type of creativity is an attribute of a teacher who is enthusiastic about teaching (Kunter et al, 2008 ). This effect is only amplifi ed when students have negative experiences with their instructor and/ or the subject (Alsharif & Qi, 2014 ). Kirikkaya ( 2011 ) looked at enthusiasm from the students' perspective.…”
Section: Enthusiasm As a Powerful Teacher Attributementioning
confidence: 99%